Noncovalent Association and Partitioning of Some Perfume Components at Infinite Dilution with Myelin Basic Protein Pseudophase in Normal Saline - Tahir, Ume (Langmuir : the ACS journal of surfaces and colloids, 2021)
Myelin basic protein (MBP), one of the major protein constituents of the myelin sheath, possesses unique ligand-binding features. We present a novel equilibrium headspace gas chromatographic technique to examine the thermodynamics of noncovalent interactions between common perfume components: Lilial, Hedione, Hexylcinnamic aldehyde, and Versalide with MBP monomers and its hexameric MBP-pseudophase. A general theoretical model is used to calculate the critical aggregation concentration (cac) of MBP, perfume component binding constants with monomeric MBP, K11, and MBP as pseudophase, Kn1, and free energies for perfume component binding with monomeric MBP, ΔGb,11, and MBP as pseudophase, ΔGb,n1. In addition, the pseudophase-water partition coefficients, Kx, the free energies of transfer of perfume from bulk water to the MBP-pseudophase, ΔGt, and the intra-aggregate activity coefficients, γm∞, at infinite dilution were also determined. The cac value measured by the method of fractional distribution is a unique and precise approach in understanding the aggregation phenomenon. Within the experimental error, the 1:1 binding free energies did not differ by more than 1 kJ/mol among the perfume components but favored the MBP pseudophase binding by 6 kJ/mol. Therefore, that protein aggregation can enhance the binding of small molecules is probably a general conclusion. While the magnitudes of K11, Kn1, ΔGb, Kx, and ΔGt show weak trends, the γm∞ values show a strong and distinct trend in interaction, spanning 4 orders of magnitude among the perfume components